The Relationship Between the Implementation of Electronic Medical Records and Work Effectiveness at Arjawinangun Regional General Hospital, Cirebon Regency, in 2026 - Rikza, Aisiyah Haura; Mohammad, Maula Ismail; Elfi; Subianto, Totok (LPPM Universitas Dhyana Pura, 2026)
Electronic Medical Records (EMR) are implemented to improve work effectiveness in hospitals. However, several obstacles are still found in their implementation, such as limited infrastructure, non-integrated systems, and differences in user capability. This study aims to analyze the relationship between EMR implementation and the work effectiveness of EMR users at RSUD Arjawinangun, Cirebon Regency. This study used a quantitative method with a correlational analytic design and a cross-sectional approach. The sample consisted of hospital staff using EMR selected by Disproportionate Stratified Random Sampling based on inclusion criteria. The study instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included univariate and bivariate analysis using the Chi-Square test. The results showed that most respondents assessed EMR implementation as good (71.6%), while 28.4% assessed it as poor. Work effectiveness was mostly categorized as good (77.3%) and 22.7% as poor. The Chi-Square test result showed a p-value of 0.007 (p < 0.05), indicating a significant relationship between EMR implementation and work effectiveness. In conclusion, there is a significant relationship between EMR implementation and work effectiveness. Good EMR implementation supports the improvement of work effectiveness, accuracy, and more structured patient data management.